Impact of 2 Distinct Levels of Mean Arterial Pressure on Near-Infrared Spectroscopy During Cardiac Surgery: Secondary Outcome From a Randomized Clinical Trial. (June 2019) - Holmgaard, Frederik; Vedel, Anne G.; Lange, Theis; Nilsson, Jens C.; Ravn, Hanne B.
Abstract : BACKGROUND: Near-infrared spectroscopy (NIRS) is used worldwide to monitor regional cerebral oxygenation (rScO2 ) during cardiopulmonary bypass (CPB). Intervention protocols meant to mitigate cerebral desaturation advocate to increase mean arterial pressure (MAP) when cerebral desaturation occurs. However, the isolated effect of MAP on rScO2 is uncertain. The aim of the present study was in a randomized, blinded design to elucidate the effect of 2 distinct levels of MAP on rScO2 values during CPB. We hypothesized that a higher MAP would be reflected in higher rScO2 values, lower frequency of patients with desaturation, and a less pronounced cerebral desaturation load. METHODS: This is a substudy of the Perfusion Pressure Cerebral Infarct trial, in which we investigated the impact of MAP levels during CPB on ischemic brain injury after cardiac surgery. Deviation in rScO2 was a predefined outcome in the Perfusion Pressure Cerebral Infarct trial. Patients were randomized to low MAP (LMAP; 40–50 mm Hg) or high MAP (HMAP; 70–80 mm Hg) during CPB. CPB pump flow was fixed at 2.4 L/min/m 2, and MAP levels were targeted using norepinephrine. Intraoperatively, NIRS monitoring was performed in a blinded fashion, with sensors placed on the left and right side of the patient's forehead. NIRS recordings were extracted for offline analysis as the mean value of left and right signal during prespecified periods. Mean rScO2 during CPB was defined as the primary outcome in the present study. RESULTS: The average MAP level during CPB was 67 mm Hg ± SD 5.0 in the HMAP group (n = 88) and 45 mm Hg ± SD 4.4 in the LMAP group (n = 88). Mean rScO2 was significantly lower in the HMAP group during CPB (mean difference, 3.5; 95% confidence interval, 0.9–6.1; P = .010). There was no difference in rScO2 values at specified time points during the intraoperative period between the 2 groups. Significantly more patients experienced desaturation below 10% and 20% relative to rScO2 baseline in the HMAP group ( P = .013 and P = .009, respectively), and the cerebral desaturation load below 10% relative to rScO2 baseline was more pronounced in the HMAP group ( P = .042). CONCLUSIONS: In a randomized blinded study, we observed that a higher MAP induced by vasopressors, with a fixed CPB pump flow, leads to lower mean rScO2 and more frequent and pronounced cerebral desaturation during CPB. The mechanism behind these observations is not clear. We cannot exclude extracranial contamination of the NIRS signal as a possible explanation. However, we cannot recommend increasing MAP by vasoconstrictors during cerebral desaturation because this is not supported by the findings of the present study.